Befriending the body through clothes: the role of clothing in secular and religious women’s body appreciation - Stolovy, Tali (Frontiers in Psychology, 2024)
Women invest in their appearance through clothes, and the way they view their bodies translates into how they choose to dress. Nonetheless, body image research often overlooks the role of clothing in fostering body appreciation. This study examined the impact of a psychoeducational feministic course on the sociology and psychology of attire, on students' clothing functions and body appreciation.The participants were 114 female MA students (47 secular, 67 religious) between the ages of 24 and 64 who completed the Body Appreciation Scale (Avalos et al. 2005) and Function of Clothing scale (Kwon & Parham, 1994) at the beginning and end of the course.The results support the contribution of the course to changes in participants' clothing functions and improvement in their body appreciation F(1,96) = 32.33, p < .001, partial Eta squared = .25. Surprisingly, religiousness had no impact on the results.This research contributes to the field of positive body image by presenting the potential role of clothing in fostering body appreciation among women. It demonstrates the benefits of investing in clothing that are less driven by external standards and more by the expression of valued aspects of the self.